Pengaruh Gender Diversity dan Firm Size Terhadap Financial Distress pada Perusahaan Sektor Tekhnologi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Miriyati A. Husain; Yayu Isyana Pongoliu; Idham Masri Ishak (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to find out how much influence gender diversity and company size have on financial distress in technology companies listed on the Indonesian Stock Exchange (BEI). Using a purposive sampling technique from a population of 47 companies with a sample of 15 companies that met the research criteria. The analytical method used is logistic regression analysis using the IBM SPSS 26 application as a statistical and hypothesis testing tool. The results obtained from this research indicate that the variables gender diversity and company size do not simultaneously influence financial distress. Meanwhile, the gender diversity variable partially does not have a significant effect on financial distress, where this company relies more on focusing on improvement by carrying out good performance management by presenting the potential of each existing board. With diversity, it can make the company work together, both with women and men. man. man. To achieve company survival. Meanwhile, partial company size does not have a significant effect on financial distress because companies that have large total assets can make it easier for the company to continue to develop and prove that the company has good performance in achieving its goals. The large total assets owned by the company can make it possible for this to happen. the incidence of bankruptcy is very small.